2020
DOI: 10.19173/irrodl.v21i3.4638
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Scaffolding Effects in Online Learning in Higher Education

Abstract: The significance of scaffolding in education has received considerable attention. Many studies have examined the effects of scaffolding with diverse groups of participants, purposes, learning outcomes, and learning environments. The purpose of this research was to conduct a meta-analysis of the effects of scaffolding on learning outcomes in an online learning environment in higher education. This meta-analysis included studies with 64 effect sizes from 18 journal articles published in English, in eight countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 33 publications
(36 reference statements)
0
60
2
5
Order By: Relevance
“…These pieces of writing were the main focus of the course and involved students completing an individual paper related to their own area of research interest. The present study's results do not support research that shows that collaboration can help students notice gaps in their knowledge and allows scaffolding and feedback from other learners (Doo et al, 2020). However, the present study's results do correspond to those of Leidner and Fuller (1997), who found that although students who worked in collaborative groups expressed more interest in the learning content and perceived learning, while students who worked individually exhibited better learning performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These pieces of writing were the main focus of the course and involved students completing an individual paper related to their own area of research interest. The present study's results do not support research that shows that collaboration can help students notice gaps in their knowledge and allows scaffolding and feedback from other learners (Doo et al, 2020). However, the present study's results do correspond to those of Leidner and Fuller (1997), who found that although students who worked in collaborative groups expressed more interest in the learning content and perceived learning, while students who worked individually exhibited better learning performance.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the cognitive transactional cost as well as retrieval strategy disruption, the act of working in groups has the potential to aid practice and performance of a task. Through the activity itself, participants in a group may recognize gaps in their own learning and seek guidance from their peers (Doo et al, 2020;Shin et al, 2020). Those more knowledgeable about a subject may give information or suggestions, such as ways to approach a goal or an explanation for information another student finds confusing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scaffolding activities throughout the semester (Fig. 1 ) to prepare students for the research project proved particularly important for an online lab course [ 12 ]. The semester began with students participating in workshops on topics such as analytical figures of merit and calibration, spectroscopy, and statistical analysis.…”
Section: Student Research Projects Within An Online Analytical Chemismentioning
confidence: 99%
“…Most previous studies on online education have focused on the socialization process. These studies have emphasized socialization performance, such as lecture satisfaction and learning effects [4]. Unlike such studies focused on socialization performance, this paper focuses on individual growth.…”
Section: Introductionmentioning
confidence: 99%